Characterization of SnO2 thin films deposited on glass by flashing spray pyrolysis for Grätzel-type solar cells (Superficies y Vacío, 2013)
SnO2 thin films were deposited on glass substrates by intermittent spray pyrolysis technique, using solution of SnCl45H2O in methanol. Thin films obtained were characterized by X-Ray Diffraction (XRD), UV-VIS spectroscopy, Scanning Electron Microscopy (SEM) and resistivity measurements by Van der Pauw method. According to results, high transmittance in visible light spectrum, cassiterite phase of SnO2 and uniformity of the film across the substrate were determined. Optical, electrical and structural features obtained in material synthesis are appropriate for electrodes in Grätzel solar cells such as high transmittance (>80%), low resistivity (9.28 x 10-03 ?.cm) and high density of carriers (6.24 x 1019 cm-3). Thickness of the film was determined based on transmittance spectra and the crystallite size from XRD diffractogram by Scherrer’s equation.